2016
DOI: 10.1080/09638288.2016.1250118
|View full text |Cite
|
Sign up to set email alerts
|

Return to work following acquired brain injury: the views of patients and employers

Abstract: Both patients and employers mentioned work-related and patient-related facilitators, work-related and condition-related barriers, and work-related solutions to RTW-problems. Patients mentioned lack of guidance and support as barriers, and stressed the need for understanding and acceptance of the limitations resulting from ABI in any RTW-solution. Implications for rehabilitation •Patients and employers are important stakeholders in the return to work (RTW) process of a patient with acquired brain injury (ABI) •… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 23 publications
3
44
0
1
Order By: Relevance
“…Earlier research has confirmed the importance of psychosocial information, motivational support and practical advice (20). It is important that RTW programmes address psychosocial aspects (21,22).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Earlier research has confirmed the importance of psychosocial information, motivational support and practical advice (20). It is important that RTW programmes address psychosocial aspects (21,22).…”
Section: Discussionmentioning
confidence: 98%
“…Early information may lead to a clearer picture of the person's abilities and limitations and facilitate the RTW process according to the fourth subcategory. With improved knowledge, patients can, in their turn, provide improved information to their employers, co-workers and relatives, who may also need stroke-related information (10,21). Brochures and e-health tools (28) can be developed to inform employers, relatives and other stakeholders about the consequences of stroke.…”
Section: Journal Of Rehabilitation Medicinementioning
confidence: 99%
“…They perceived that it was difficult to manage both work, taking care of the family and household chores. The impact of the home situation on work has previously been described among persons with traumatic brain injuries [36]. After stroke, the need and extent of practical help in the home situation is not so often highlighted in the literature, but needs to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult following a brain injury to return to paid work due to the resulting psychosocial, cognitive, psychological, communication and/or physical difficulties, which often have a negative effect on an individual's ability to seek or maintain employment (Donker-Cools et al, 2018;Schonbrun et al, 2007). Saltychev et al (2013) suggest that returning to work and maintaining employment following a life-changing event, such as a traumatic brain injury, can be challenging due to the complex interaction of the potential resulting physical, cognitive and emotional impairments.…”
Section: Research Rationalementioning
confidence: 99%